Essential thrombocytosis: review of literature with a rare presentation of cerebral thrombosis treated with endovascular therapy - Datla, Aravind V.; Dalai, Sibasankar (International Journal of Research in Medical Sciences, 2021)
Essential thrombocytosis (ET) is a clonal hematopoietic stem cell disorder. Clinically there is an over-production of platelets without a definable cause. ET is a myeloproliferative neoplasm (MPN). It has an incidence of 1 to 2 per 100,000 population and a distinct female predominance. Once considered a disease of the elderly and responsible for significant morbidity due to haemorrhage or thrombosis, it is now clear that ET can occur at any age in adults and often without symptoms or disturbances of hemostasis. ET can cause both thrombosis or haemorrhage and carries a risk of acute leukemic transformation. Being an MPN, in some cases, polycythemia vera (PV) or primary myelo-fibrosis (PMF) can present as ET. Though the average life expectancy only slightly deviates from the standard expected for age-matched individuals, a thorough understanding of its etiopathogenesis, clinical presentation, complication and management can make a world of difference to patients. Thrombosis is one such complication that has a significant impact on the mortality and morbidity of ET. We proposed using endovascular therapy (EVT) as a treatment modality for cerebral venous sinus thrombosis.